The requirement for liquidated damages - Espinoza Espinoza, Juan (2014)
The requirement for liquidated damages a convention, accessorial  to  the principal obligation, which guarantees the accomplishment of the first one. The penalty clause has received a different treatment in various legal systems; such are the French, Italian, German and Peruvian cases.In this article, the author explains the functions of the requirement for liquidated damages and its differences with similar figures. In addition he explains the relation between the requirement for liquidated damages and precontractual responsibility, as well as its role inthe scheme of contractual responsibility.